An effective control structure of on-board battery charger for electric vehicles - Mohammad Khadem; Mohammad Karami (International Journal of Advances in Applied Sciences, 2022)
The plug-in electric vehicles (PEVs) including plug-in hybrid electric and all-electric vehicles will play a key role in the transportation future throughout the world. Consequently, a variety of works must be done to decrease the cost, improve the structure and increase the convenience of PEVs. This study proposed a single-phase, non-isolated and on-board battery charger with no use of any transformer which reduced the volume and weight of the system for PEVs. The main purpose is to provide an accurate control structure in order to achieve an acceptable charging in the wide range of voltage. The proposed structure is simulated by matrix laboratory (MATLAB) software. The results showed a high-power density, high efficiency and appropriate power factor from the structure of the non-isolated and single-phase charger.